ANALISIS DAN PERANCANGAN ONLINE ANALYTICAL PROCESSING SEBAGAI BUSINESS INTELLIGENCE PADA SEKOLAH MUSIK CANTATA - Yunus Fadhillah (Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
Cantata Music School is the object of the research conducted by the author. In the process of collecting data and information through direct observation and interviews with the relevant part is Managing Director and IT support Cantata Music School. The use of a database using the original structure of the historical data Cantata academic information systems.Â The results of the research conducted was a